Tourist season - Weaver, Brynne (Weaver, Brynne,- Seasons of carnage., 2025)
"Cape Carnage is a seaside town of colorful houses, quirky shops, and an unusually high body count. With tourists comes trouble, and Harper Starling won't let anyone ruin her picture-perfect home. A skilled gardener with killer instincts, Harper protects her sanctuary--and her aging mentor with a fading memory--at any cost. Troublesome tourists don't check out of Carnage. They compost beneath Harper's award-winning flowerbeds. But Nolan Rhodes isn't your average tourist. Devilishly handsome, disarmingly charming, and skilled with a blade, Nolan is relentless in the pursuit of revenge. On every anniversary of the hit-and-run accident that fractured his life, Nolan slays another target. And he's saved the best for last: the undeniably beautiful Harper Starling. The problem? Harper isn't the monster he expected. And she won't go down without a fight. When an amateur true crime investigator comes to Cape Carnage on the trail of a long-lost serial killer, Harper and Nolan strike an uneasy truce. If Nolan helps Harper protect her town, she'll keep quiet about his hunting habits . . . for now. But their alliance soon spirals into obsession, one that threatens to shatter every secret in Carnage--including their fragile love."--Dust jacket flap.